Mucocele of appendix unmasking appendiceal neoplasm - S. P., Gayathre; Kalaiselvi; Rajeswaran, Tharani (International Surgery Journal, 2023)
An appendiceal neoplasm is rare among all the gastrointestinal tumors. An appendiceal mucocele is a dilatation of the appendix due to a benign or malignant disease, which causes the obstruction of the appendix and consequent accumulation of mucus secretion. Mucinous malignancy of the appendix represents a low occurrence among appendiceal neoplasms. The preoperative diagnosis is difficult due to non-specific clinical manifestations of the disease. Preoperative investigations may be inconclusive for diagnosis at times. Management is based on the size and grade of the tumor. We had two female patients who presented with poorly defined symptoms in whom, radiological evidences showed appendiceal dilatation. Both the patients when proceeded with laparotomy, had no peritoneal spillage, and were subjected to right hemicolectomy. Based on the grade of the tumor, adjuvant management was planned. Both the patients had favorable outcomes following treatment.